Transformational Leadership Practices in Professional Management of Deltras Football Club: Praktik Kepemimpinan Transformasional dalam Pengelolaan Profesional Klub Sepak Bola Deltras - Wisnu Panggah Setiyono; Fahmi Andika (Indonesian Journal of Law and Economics Review, 2025)
General Background: Professional football management increasingly requires structured governance, strategic planning, and accountable leadership to sustain competitiveness. Specific Background: Deltras FC Sidoarjo has undergone managerial transformation aimed at establishing professional standards in organizational operations. Knowledge Gap: Empirical evidence regarding leadership implementation in mid-tier Indonesian clubs remains limited, particularly at the Liga 2 level. Aims: This study analyzes how leadership style is implemented by club management to organize operations professionally. Results: Using a descriptive qualitative approach with interviews, observations, and documentation, findings indicate the adoption of transformational and participatory leadership characterized by clear vision formulation, open communication, player involvement in decision-making, professional organizational structuring, financial transparency, and strengthened relations with supporters and sponsors. These practices correspond with improved internal satisfaction, operational efficiency, and competitive performance. Novelty: The research provides a contextual case study of leadership practices in a regional football club, offering practical evidence beyond top-tier teams. Implications: The findings contribute to sport management literature and provide guidance for similar clubs seeking sustainable governance, stakeholder trust, and structured organizational development. Keywords: Transformational Leadership, Football Club Management, Organizational Professionalism, Stakeholder Loyalty, Sport Governance Key Findings Highlights: Clear strategic vision guides coordinated managerial actions Participatory decision processes strengthen internal commitment Transparent administration supports sustainable club operations